Antiribonuclease H2 antibodies are an immune biomarker for systemic lupus erythematosus. (19th May 2017) - Nozawa, Kazuhisa; Doe, Kentaro; Uomori, Kaori; Sekigawa, Iwao; Takasaki, Yoshinari; Yamaji, Ken; Tamura, Naoto
Abstract: We previously reported that autoantibodies against the proliferating cell nuclear antigen protein (PCNA)-binding protein chromatin assembly factor-1 (CAF-1) are specifically found in patients with systemic lupus erythematosus (SLE). PCNA and its complex constituents elicit autoimmune responses in patients with SLE, suggesting that autoantibody diversification likely occurs owing to epitope spreading. Therefore, we sought to clarify whether patients with SLE exhibit an autoimmune response to Ribonuclease H2 (RNase H2), another PCNA-binding protein that regulates cell division. As results, RNase H2 autoantibodies were detected in the sera of 33.9% (19/56) of SLE patients, which was significantly higher than that observed in sera from other patients with systemic autoimmune diseases (polymyositis/dermatomyositis, systemic sclerosis, Sjogren's syndrome, mixed connective tissue disease and rheumatoid arthritis) and healthy controls. Regression analysis also showed that serum anti-RNase H2 levels were strongly correlated to that of CAF-1 in SLE patients. Our data support the use of RNase H2 autoantibodies as a serum biomarker for SLE diagnosis. Moreover, the strong correlation observed between RNase H2 and CAF-1 suggests that intermolecular epitope spreading may play a critical role in autoantibody production and diversification in SLE.